Earlier accumulation of calcium, phosphorus, and magnesium in the coronary artery in comparison with the ascending aorta, aortic valve, and mitral valve - Yoshiyuki Tohno (2018)
To explore reasons for a high accumulation of Ca and P occurring in the coronary artery of Thai with aging, the authors investigated agerelated changes of elements in the coronary artery, ascending aorta near the heart, and cardiac valves in single individuals, and the relationships in the elements between the coronary artery and either the ascending aorta or cardiac valves. After an ordinary dissection by medical students at Chiang Mai University was finished, the anterior descending arteries of the left coronary artery, ascending aortas, mitral valves, and aortic valves were resected from the subjects. The subjects consisted of 17 men and 9 women, ranging in age from 46 to 76 yr. The element content was analyzed by inductively coupled plasma-atomic emission spectrometry. The average content of Ca and P was the highest in the coronary artery and decreased in the order aortic valve, ascending aorta, and mitral valve. The Ca, P, and Mg content increased in the coronary artery in the fifties and in the ascending aorta, aortic valve, and mitral valve in the sixties. It should be noted that the accumulation of Ca, P, and Mg occurred earlier in the coronary artery than in the ascending aorta, aortic valve, and mitral valve. It was found that with respect to the Ca, P, Mg, and Na contents, the coronary artery correlated well with both the aortic valve and ascending aorta, especially with the aortic valve, but it did not correlate with the mitral valves. This finding suggests that the accumulation of Ca, P, Mg, and Na occurs in the coronary artery together with the aortic valve and ascending aorta, but not together with the mitral valve. Because regarding the accumulation of Ca, P, and Mg, the ascending aorta and aortic valve are preceded by the coronary artery, it is unlikely that the accumulation of Ca, P, and Mg spreads from the ascending aorta or aortic valve to the coronary artery. © Copyright 2006 by Humana Press Inc. All rights of any nature, whatsoever, reserved.